Activating the most disadvantaged youth in Switzerland: Administratively too risky, politically too costly?. (30th October 2018) - Pisoni, Delia
Abstract: To increase the chances of integrating youth into labour markets in contemporary European knowledge societies, many policy schemes are geared towards investing in youth's human capital. Since apprenticeship systems are assumed to ease school‐to‐work transitions, this seems a particularly promising avenue. However, research highlights that social policies often do not reach the most disadvantaged members of society. The aim of this article is to shed light on the reasons and mechanisms causing this phenomenon, called the Matthew effect, through a single, embedded case study of a vocational education and training programme for disadvantaged youth in Switzerland. The findings highlight cream‐skimming practices as a coping strategy enabling frontline workers to satisfy strict assessment criteria. A budgetary allocation driven politico‐administrative logic promotes such practices as a means to generate solid results, so as to safeguard political – and thus financial – support.